INFLUENCE OF CUSTOMER COMPLAINTS MANAGEMENT STRATEGIES ON CUSTOMER SATISFACTION IN MTN NIGERIA - Okafor, Ozoemena Christian; Ogbuke, John Chukwudi; Okafor, Juliana Nkechi (International Journal of Allied Research in Marketing and Management (IJARMM), 2024)
The study examined the influence of customer complaints management strategies on customer satisfaction in MTN Nigeria. The specific objectives include to; examine the influence of complaint-handling staff attitude on customer satisfaction in MTN Nigeria in Enugu metropolis. Examine the influence of customer service waiting time on customer satisfaction in MTN Nigeria in Enugu metropolis and examine the influence of service failure compensations on customer satisfaction in MTN Nigeria in Enugu metropolis. A descriptive survey design was adopted for the study. The population of the study was 97,700 MTN customers. The sample size of the study was 398 using Taro Yamani Formula. Questionnaire instrument was validated. Reliability of the instrument was checked using Cronbatch alpha test. The study used convenience sampling techniques for selecting respondents. The findings revealed that complaint-handling staff attitude had a significant positive influence on consumer satisfaction in MTN Nigeria in Enugu metropolis. customer service waiting time had a significant positive influence on consumer satisfaction in MTN Nigeria in Enugu metropolis and service failure compensations had a significant positive influence on consumer satisfaction in MTN Nigeria in Enugu metropolis. We concluded that customer complaints management strategies of MTN, specifically complaint-handling staff attitude, customer service waiting time and service failure compensations are major drivers of customer loyalty in MTN. based on findings, the study recommended that complaint-handling staff attitude should be improved, customer service waiting time should be highly reduced and MTN compensations should be fair when customers suffer losses or injury of any kind.